Blast effects on buildings - Cormie, David; Mays, Geoffrey; Smith, P. D., 1950 March 26- (Thomas Telford, 2009)
Revised and augmented to reflect significant developments in the field of blast engineering since the early 1990s, this 2nd edition includes industry-accepted methods for the design of glazing to resist blast loading, as well as a new chapter on hostile vehicle mitigation techniques. Guidance on structural steelwork and reinforced concrete design is extended and enhanced, supplemented with material on design in new materials such as steel-concrete-steel composites.